Common genetic polymorphisms contribute to the association between chronic lymphocytic leukaemia and non-melanoma skin cancer. (22nd March 2021) - Besson, Caroline; Moore, Amy; Wu, Wenting; Vajdic, Claire M; de Sanjose, Silvia; Camp, Nicola J; Smedby, Karin E; Shanafelt, Tait D; Morton, Lindsay M; Brewer, Jerry D; Zablotska, Lydia; Engels, Eric A; et al.
Abstract: Background: Epidemiological studies have demonstrated a positive association between chronic lymphocytic leukaemia (CLL) and non-melanoma skin cancer (NMSC). We hypothesized that shared genetic risk factors between CLL and NMSC could contribute to the association observed between these diseases. Methods: We examined the association between (i) established NMSC susceptibility loci and CLL risk in a meta-analysis including 3100 CLL cases and 7667 controls and (ii) established CLL loci and NMSC risk in a study of 4242 basal cell carcinoma (BCC) cases, 825 squamous cell carcinoma (SCC) cases and 12802 controls. Polygenic risk scores (PRS) for CLL, BCC and SCC were constructed using established loci. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Results: Higher CLL-PRS was associated with increased BCC risk (OR4th-quartile-vs-1st-quartile = 1.13, 95% CI: 1.02–1.24, P trend = 0.009), even after removing the shared 6p25.3 locus. No association was observed with BCC-PRS and CLL risk ( P trend = 0.68). These findings support a contributory role for CLL in BCC risk, but not for BCC in CLL risk. Increased CLL risk was observed with higher SCC-PRS (OR4th-quartile-vs-1st-quartile = 1.22, 95% CI: 1.08–1.38, P trend = 1.36 × 10 –5 ), which was driven by shared genetic susceptibility at the 6p25.3 locus. Conclusion: These findings highlight the role of pleiotropy regarding the pathogenesis of CLL and NMSC and shows that a single pleiotropic locus, 6p25.3, drives the observed association between genetic susceptibility to SCC and increased CLL risk. The study also provides evidence that genetic susceptibility for CLL increases BCC risk.